A biomechanical study of locking spongious screws and failure rates are higher than expected in plate fixation - Fatih Parmaksizoglu; Onur Cetin; Sinan Kilic; Yener Ince (Scientific Reports)
Abstract Locking plates have a rapidly growing process especially in the past decades and results are satisfactory especially in the osteoporotic bones compared to non-locking compression plates. There are many forms of failure in the fracture fixation of locking plates, and screw pull-out is one of the main failure reasons. In this study, we aim to investigate pull-out failure in locking plates using locking spongious screws. The pull-out force of an FDA approved locking plate system (LPS) and anonymous locking plate using the single lead head locking spongious screw (LPuLSS) was evaluated in vitro on the PCF-15 and PCF-10 osteoporotic sawbone models. A total of 28 individual plate-bone models were tested and pull-out force was evaluated on a distraction machine. The moment of separation of the screws from the bone blocks was noted. In the first study using PCF15 bone model, in Group 1, the pull-out force has an average of 606.82 N. In Group 2, the pull-out force has an average of 294.15 N. According to these results, Group 1 adhere to the bone model 206.29% more strongly than those in Group 2 (P = 0.025). In the second study using PCF 10, in Group 3, the average pull-out force was 166.50 N and in Group 4 the average was 42.83 N. According to these results, Group 3 adhere to the bone model 388.74% more strongly than those in Group 4 (P = 0.002). Locking plates are mostly used in osteoporotic bones and this study demonstrated that the single lead head locking spongious screws which is currently used worldwide have a serious technical problem which arouses with difference of the thread pitch distances on the body and on the head causes pull-out failure.